The effect of a sand surface on physical performance responses of junior male handball players to plyometric training - Mehrez Hammami; Nicola Luigi Bragazzi; Souhail Hermassi; Nawel Gaamouri; Ridha Aouadi; Roy J. Shephard; Mohamed Souhaiel Chelly (BMC, 2020)
Abstract Background The effects of 7 weeks plyometric training on a stable surface and on sand were compared in junior male handball players. Methods A team of experienced players was divided randomly between three groups, undertaking a standard in-season regimen (C, n = 10), or supplementing this regimen by plyometric training on sand (PS, n = 11) or a stable surface (P, n = 10) for 7 weeks. Assessments included 20 m sprint times, change of direction tests (Modified change-of-direction T-test and Modified Illinois test), a repeated sprint T-test, jumping ability (squat, countermovement and five jump tests), and static and dynamic balance. Results After the intervention, PS showed significant increases of sprint speed relative to P and C. Change of direction scores were also improved for PS relative to P and C. Both PS and P increased vertical jump performance (squat jump, p = 0.005; ES = 0.170; counter-movement jump p < 0.001; ES = 0.247). Repeated sprint T-test scores improved in PS and P relative to C, with best times of PS > P (p < 0.05). Both plyometric groups improved their dynamic balance (p < 0.05), with three parameters of PS and only one of P being significantly greater than C. Static balance was also enhanced in both experimental groups (PS > P). Conclusions We conclude that for reasons that remain to be clarified, several performance measures in adolescent male handball players were increased more by 7 weeks of PS than by P.